Hubungan Tingkat Kecemasan Ibu Hamil Dengan Kepatuhanantenatal Care Selama Pandemi Covid-19 Di Wilayah Kerja Puskesmas Andalas Kota Padang - Rika Syafitri; Chichi Hafifa Transyah; Rahma Gustika (Jurnal Amanah Kesehatan, 2022)
In indonesia in 2021 cases of pregnant womwn confirmed positive for covid-19 as many as 536 cases. Meanwhile, data from the Andalas Health Center has 19 confirmed cases of covid-19 from january to june 2022. The result of the initial survey of researchers through interviews, pregnant women experience anxiety because the immune system of pregnant women is easily weak, therefore pregnant women afraid to be swab which makes pregnant women do not want to check their pregnancy, the large crowd also makes pregnant women even more anxious to do antenatal care check. The purpose of this study was to determine the relationship between the anxiety level of pregnant women and antenatal care compliance during the covid-19 pandemic in the Andalas Public Health Center Padang City. This type of research is quantitative with a cross sectional study design. This research was conducted in the work area of Andalas Public Health Center. The population in this study was pregnant women in the third trimester who were the targets of antenatal care compliance with a sample size of 73 from 7 villages taken by proportional random sampling. The data obtained were analyzed univariately with frequency distribution and bivariate with chi-square statistical test. the result of the univariate study showed that 46 pregnant women (63%) were obedient and 68 pregnant women (93,2%) did not experience anxiety. The result of the bivariate study based on statistical tests showed that there was a relationship between the anxiety level of pregnant women and antenatal care compliance p=0,011(p≤0,05). It is suggested to the Andalas Public Health Center as an input in an effort to increase counseling about antenatal care examinations.